Group Communication Of Mudo Laras Karawitan Community IN Maintaining Cultural Existence : Komunikasi Kelompok Komunitas Karawitan Mudo Laras Dalam Mempertahankan Eksistensi Budaya - Wilujeng, Agustina Rachma; Sinduwiatmo , Kukuh (Universitas Muhammadiyah Sidoarjo, 2024)
Group communication is the most important thing in a community, starting from a common interest and followed by a process of interaction between members to achieve a common goal. Mudo Laras Karawitan Community is one of the youth associations in Balerejo Village, Wlingi Sub-district, Blitar Regency that plays a role in preserving and developing traditional culture among the younger generation. Karawitan, as a Javanese traditional music art that requires close collaboration among community members, through compact group communication can produce harmony in the presentation of the music performed. This research aims to understand the group communication of the Mudo Laras Karawitan community as seen from the interaction between members and the communication network that is built. This research uses group achievement theory with the application of descriptive qualitative research techniques. Purposive sampling strategy was used in the selection of informant subjects. Interview, documentation, and observation methods were used in the data collection process. The results showed that group communication occurs directly (face-to-face) between members in the Mudo Laras community. In it there is an exchange of messages by discussing the rules as well as forming a generation to continue the existing traditions. This community does not have a leader, all members have the same portion interacting with all members without any restrictions so that it is formed.